Decision making on vestibular schwannoma treatment: predictions based on machine-learning analysis - Profant, Oliver; Bureš, Zbyněk; Balogová, Zuzana; Betka, Jan; Fík, Zdeněk; Chovanec, Martin; Voráček, Jan (Scientific reports, 2021)
Decision making on the treatment of vestibular schwannoma (VS) is mainly based on the symptoms, tumor size, patient's preference, and experience of the medical team. Here we provide objective tools to support the decision process by answering two questions: can a single checkup predict the need of active treatment?, and which attributes of VS development are important in decision making on active treatment? Using a machine-learning analysis of medical records of 93 patients, the objectives were addressed using two classification tasks: a time-independent case-based reasoning (CBR), where each medical record was treated as independent, and a personalized dynamic analysis (PDA), during which we analyzed the individual development of each patient's state in time. Using the CBR method we found that Koos classification of tumor size, speech reception threshold, and pure tone audiometry, collectively predict the need for active treatment with approximately 90% accuracy; in the PDA task, only the increase of Koos classification and VS size were sufficient. Our results indicate that VS treatment may be reliably predicted using only a small set of basic parameters, even without the knowledge of individual development, which may help to simplify VS treatment strategies, reduce the number of examinations, and increase cause effectiveness.
Keywords: senioři; Clinical Decision-Making; rozhodovací stromy; Disease Management; Reproducibility of Results; určení symptomu; reprodukovatelnost výsledků; Hearing; Middle Aged; ROC Curve; Supervised Machine Learning; mužské pohlaví; Hearing Tests; Adult; sluch; management nemoci; Neuroma, Acoustic; ROC křivka; klinické rozhodování; sluchové testy; řízené strojové učení; Decision Trees; ženské pohlaví; Humans; Machine Learning; vestibulární schwannom; lidé středního věku; dospělí; Female; Aged; Symptom Assessment; lidé; Male; strojové učení